2011
DOI: 10.1111/j.1365-2893.2010.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and route of HCV infection can influence the associations of HLA with viral clearance in an ethnically heterogeneous population

Abstract: Approximately 20% of hepatitis C virus (HCV) infected individuals clear the virus. Host factors that influence the course of HCV infection are still under investigation, and the data on the association of human leukocyte antigen (HLA) alleles and HCV clearance are scarce and controversial. The aims of this study were to investigate whether HLA alleles are associated with clearance of HCV infection in a highly admixed Brazilian population and whether these associations could be influenced by ethnicity and route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Another possible explanation could be a difference in the route of HCV transmission. Several previous studies have suggested that the route of contamination may influence the relationship between some HLA alleles and viral clearance, and that there might be an additional factor responsible for the large variation of the results in studies of HLA and HCV clearance [Harris et al, ; de Almedia et al, ]. The thalassemia patients whom participated in the present study had received a high infectious dose of virus during blood transfusion.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Another possible explanation could be a difference in the route of HCV transmission. Several previous studies have suggested that the route of contamination may influence the relationship between some HLA alleles and viral clearance, and that there might be an additional factor responsible for the large variation of the results in studies of HLA and HCV clearance [Harris et al, ; de Almedia et al, ]. The thalassemia patients whom participated in the present study had received a high infectious dose of virus during blood transfusion.…”
Section: Discussionmentioning
confidence: 79%
“…The association of HLA class II alleles with HCV outcome among various ethnic populations in different geographical regions of the world has been reported. However, the results have been remarkably variable [Azocar et al, ; Ksiaa et al, ; Singh et al, ; de Almedia et al, ]. For example, Ksiaa et al [] reported that while DRB1*08 was associated with HCV clearance, DRB1*15 seemed to be a risk marker for viral persistence in the Tunisian patients.…”
Section: Introductionmentioning
confidence: 99%
“…We found no difference in the IL28B polymorphism between the CHC and SVC groups, while the other studies failed to provide such information. Second, the transmission route and the exposure dose of HCV also play an important role on the spontaneous clearance . For our subjects, the transmission route was uniform (i.e., paid plasma donors); they were infected through high‐dose exposure, whereas in other studies the transmission route and the exposure dose were heterogeneous.…”
Section: Discussionmentioning
confidence: 92%
“… 38 In fact, we previously reported the influence of ethnicity on the association between human leukocyte antigens and spontaneous viral clearance of HCV. 39 …”
Section: Discussionmentioning
confidence: 99%